PENGARUH TATA KELOLA PERUSAHAAN TERHADAP TARIF PAJAK EFEKTIF - Ain, Qurrotul; Subardjo, Anang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to examine the mechanism of corporate governance to the effective taxrate (ETR). Corporate governance variable is measured by using director compensation, director shareholding,the numbers of audit committee, and audit quality. Meanwhile, the control variable in this research is measuredby using the growth rate of the company and the performance of the company. The samples are manufacturingcompanies which are listed in Indonesia Stock Exchange (BEI) in 2011 â 2013 periods. The sample collectionmethod has been done by using purposive sampling and 15 companies have been selected as samples. Meanwhile,the methods of the analysis are descriptive statistical tests, classic assumption test, multiple regressions analysis,model test, and hypothesis test. The results of the research show that (1) the director compensation hassignificant and positive influence to the effective tax rate, (2) the director shareholding has significant andnegative influence to the effective tax rate, (3) the numbers of audit committee have significant and positiveinfluence to the effective tax rate, (4) the audit quality has positive and significant influence to the effective taxrate, (5) the growth rate of the company has significant and positive influence to the effective tax rate, and (6) theperformance of the company has significant and negative influence to the effective tax rate.Keyword: Corporate Governance, Effective Tax Rate (ETR), Director Compensation, Director Shareholding,Audit Quality.